Peningkatan Kinerja Pemerintahan Melalui Good Government Governance dan Pencegahan Korupsi - Hadi, Aditya Anton Atmojo; Chariri, Anis (E-Jurnal Akuntansi; Vol 33 No 12 (2023), 2023)
Indonesia has enormous economic potential, but not been able to make the Indonesian people prosperous. This problem occurs because corrupt practices that cause loss of government resources. A good management system needs to be developed to reduce the occurrence of corruption This research aims to investigate the relationship between regional government governance, quality of corruption prevention and regional government performance in 34 provincial governments in Indonesia. This research uses Structural Equation Model (SEM) analysis with the Partial Least Square (PLS) method. This research uses secondary data from government institutions for 2021-2022. The results of this research state that the three variables have a significant positive relationship and have a causal relationship. Keywords: Good Governance; corruption prevention; government performance; Public Sector